2006
DOI: 10.1177/154193120605000329
|View full text |Cite
|
Sign up to set email alerts
|

Peer-Mediated Leap to Efficiency: Cost-Benefit Analysis in the Selection of Efficient Strategies

Abstract: There is ample evidence that computer users often do not progress from novice to expert levels of performance, particularly when efficiency is included in the definition of performance. This paper describes a theoretical argument that one of the pieces missing in the understanding of this process is an accurate assessment of how people calculate a cost/benefit analysis (CBA) of learning and using new techniques and strategies. While there are many explanations for why people often do not use accurate methods o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Another way that people can (and do) learn more advanced methods with software on the job is by working with others who use those techniques (Peres, Tamborello, Fleetwood, Chung, & Paige-Smith, 2004;Tamborello, Peres & Fleetwood, 2006;Chadwick-Dias, Tedesco, & Tullis, 2004). Indeed, in our lab we have been able to experimentally manipulate this effect and have found that people increased their utilization of more efficient methods of using the software after watching a peer use the efficient method than if they observed a peer using another method.…”
Section: Peer-to-peer Learningmentioning
confidence: 99%
“…Another way that people can (and do) learn more advanced methods with software on the job is by working with others who use those techniques (Peres, Tamborello, Fleetwood, Chung, & Paige-Smith, 2004;Tamborello, Peres & Fleetwood, 2006;Chadwick-Dias, Tedesco, & Tullis, 2004). Indeed, in our lab we have been able to experimentally manipulate this effect and have found that people increased their utilization of more efficient methods of using the software after watching a peer use the efficient method than if they observed a peer using another method.…”
Section: Peer-to-peer Learningmentioning
confidence: 99%